Central bank independence and inflation performance: panacea or placebo? - JENKINS, M.A. (PSL Quarterly Review, 2013)
A great deal of recent attention has been devoted towards the relationship between central bank independence and economic performance. The degree of central bank independence is said to determine cross-country inflation differences. However, several factors have been raised that cast doubts on such a relationship. First, the link between independence and inflation may not be as tight as previously declared. Also, predictive validity tests show that the link does not score favourably. Relevant variables also appear to have been omitted in using central bank independence as the determinant of cross-country inflation differences. This paper investigates the stylised facts regarding central bank independence and inflation performance. The structure of the labor market, the regulatory burden of the central bank and the exchange rate regime are found to be significant determinants as well. JEL Codes: E58